Fostering Competition in the Philippines : The Challenge of Restrictive Regulations - World Bank Group (World Bank, Washington, DC, 2019)
The objective of this report is to identify existing regulatory restraints to competition in key sectors and the economy as a whole and use them to design an effective competition policy for the Philippines. The report builds on Product Market Regulation (PMR) indicators and the WBG’s Markets and Competition Policy Assessment Tool (MCPAT) applied to the Philippine markets to (i) develop the main aspects of the advocacy role of the Philippine Competition Commission (PCC) against current market features; (ii) map regulatory restrictions to competition and classify them according to their effects; (iv) contextualize competition restraints within each sector to offer a set of policy recommendations; and (v) quantify the potential impact of a more pro-competitive regulatory environment for the Philippines’ economy. As the country did not have a competition law until 2015, the recently created PCC faces a challenging environment in which to implement its mandate. The two-year transitory period to start enforcement, as well as the potential to grant broad exemptions from the law under the forbearance clause, have hindered the ability of the PCC to prevent anticompetitive conduct of market players, either public or private. In this context, the advocacy role of the PCC offers a critical mechanism to address those regulatory conditions that may be enabling anticompetitive behavior. Limited market competition can stem from restrictive regulations or discretionary application of the regulatory framework that render entry and operation of new firms difficult. Ensuring government policies and regulations do not generate barriers to entry or distort the level playing field is necessary to enhance private sector participation and unlock investment opportunities.